2022
DOI: 10.22271/phyto.2022.v11.i4a.14438
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, metal content, and essential oil composition of two desert truffles species: Terfezia boudieri and Terfezia claveryi

Abstract: Terfezia species have been shown to be nutrient-dense and can be used as functional meals for human nutrition. They outperformed other diets in terms of iron, potassium, copper, and zinc. The physical features, chemical composition, and mineral content of two Terfezia species were studied. The antioxidant activity of the aqueous extract was further evaluated by assessing its radical scavenging capacity against 2, 2'-diphenyl-1-picrylhydrazyl. Terfezia samples were chemically evaluated using GC-MS to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The results showed that the respiration rate, protein content, soluble sugar content, and PPO activity in truffle fruiting bodies were gradually decreased as the storage time was increased, reaching the lowest levels in 30 d of cold storage, whereas the corruption rate, weight loss rate, TOC, and TPC were increased as the storage time was increased. These results indicated that the physicochemical properties were altered during the cold storage, largely consistent with the results previously reported ( 8 , 22 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that the respiration rate, protein content, soluble sugar content, and PPO activity in truffle fruiting bodies were gradually decreased as the storage time was increased, reaching the lowest levels in 30 d of cold storage, whereas the corruption rate, weight loss rate, TOC, and TPC were increased as the storage time was increased. These results indicated that the physicochemical properties were altered during the cold storage, largely consistent with the results previously reported ( 8 , 22 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the fruiting bodies of T. indicum are rich in nutrients, e.g., carbohydrates and proteins, their qualitative and sensory properties are only retained for a short time after harvest ( 7 , 8 ). Previous studies mainly focused on the volatile substances and antioxidant activities of T. indicum in storage, as well as the relationship between truffles and microorganisms ( 8 , 22 , 36 ). In our study, the variations of physicochemical properties and the contents of two heavy metals (Cd and Pb) of truffles during cold storage were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations